2002
DOI: 10.1046/j.1365-2745.2002.00713.x
|View full text |Cite
|
Sign up to set email alerts
|

Stress tolerance of rare and common moss species in relation to their occupied environments and asexual dispersal potential

Abstract: Summary1 Species rarity in mosses may be linked to narrow physiological tolerance and habitat specificity of established colonies and gametophyte fragments (i.e. fragments of stem apices). Stress tolerance and habitat light and moisture were compared for three rare and three common moss species. 2 Observed habitat specificity was more likely to correspond to physiology in the common species. In particular, one common species, Mnium spinulosum , was limited by intolerance of high light conditions and is charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 60 publications
0
32
0
Order By: Relevance
“…Spores of epiphytic and epixylic species have their viability reduced from around 90% to near zero after 48-240 days and 25-30 days, respectively (Egunyomi 1978;Wiklund and Rydin 2004;Maciel da Silva et al 2009). Apical gametophyte fragments maintain 80% or higher viability after 120 days in the Weld under dry storage (Cleavitt 2002(Cleavitt , 2005. In contrast, spores of Sphagnum could retain high viability (around 70%) after 3 years of burial in peat (Sundberg and Rydin 2000), and desiccated moss tubers can germinate after more than a century (H. During, personal communication).…”
Section: Evects Of Habitat and Seasonmentioning
confidence: 99%
“…Spores of epiphytic and epixylic species have their viability reduced from around 90% to near zero after 48-240 days and 25-30 days, respectively (Egunyomi 1978;Wiklund and Rydin 2004;Maciel da Silva et al 2009). Apical gametophyte fragments maintain 80% or higher viability after 120 days in the Weld under dry storage (Cleavitt 2002(Cleavitt , 2005. In contrast, spores of Sphagnum could retain high viability (around 70%) after 3 years of burial in peat (Sundberg and Rydin 2000), and desiccated moss tubers can germinate after more than a century (H. During, personal communication).…”
Section: Evects Of Habitat and Seasonmentioning
confidence: 99%
“…In contrast, species belonging to the family Mniaceae, which are common beneath closed mixedwood canopies, had reduced germination in the high light cabinet. Mnium spinulosum is intolerant of high light because of physiological limitations; its preferred habitat is shaded coniferous forest (Cleavitt 2002). Brachythecium velutinum is frequently found beneath closed forest canopies (Mills and Macdonald 2005) and was significantly less abundant in the high light cabinet, possibly reflecting a preference for reduced light levels.…”
Section: Germinated Diaspore Bank Compositionmentioning
confidence: 99%
“…To date, several moss cultivation experiments have been conducted in which gametophyte fragments are used to establish new colonies in the laboratory and field (Cleavitt, 2002;Jones and Rosentreter, 2006;Xiao et al, 2015). All of these experiments have demonstrated that artificial cultivation can accelerate the succession process of moss crusts.…”
Section: Y Guo and Y Zhao: Effects Of Storage Temperature On Desiccmentioning
confidence: 99%